Genetic Association of rs1021188 and DNA Methylation Signatures of TNFSF11 in the Risk of Conductive Hearing Loss - Bouzid, Amal; Chelly, Ameni; Tekari, Adel; Singh, Neha; Hansdah, Kirtal; Achour, Imen; Ben Ayed, Ikhlas; Jbeli, Fida; Charfeddine, Ilhem; Ramchander, Puppala Venkat; Hamoudi, Rifat; Masmoudi, Saber (Frontiers in Medicine, 2022)
Otosclerosis (OTSC) is a complex bone disorder of the otic capsule, which causes conductive hearing impairment in human adults. The dysregulation of the signaling axis mediated by the receptor activator of nuclear factor-kappa-B (RANK), RANK ligand (RANKL), and osteoprotegerin has been widely attributed to the context of metabolic bone disorders. While genetic associations and epigenetic alterations in the TNFSF11 gene (RANKL) have been well-linked to metabolic bone diseases of the skeleton, particularly osteoporosis, they have never been addressed in OTSC. This study aimed to assess whether the genetic association of rs1021188 polymorphism in the upstream of TNFSF11 and the DNA methylation changes in its promoter CpG-region reveal the susceptibility of OTSC. Peripheral blood DNA samples were collected from unrelated Tunisian-North African subjects for genotyping (109 cases and 120 controls) and for DNA methylation analysis (40 cases and 40 controls). The gender-stratified analysis showed that the TNFSF11 rs1021188 C/T was associated with OTSC in men (p = 0.023), but not in women (p = 0.458). Individuals with CC genotype were more susceptible to OTSC, suggesting an increased risk to disease development. Using publicly available data, the rs1021188 was within a cluster grouping the subpopulations with African ethnicity. Moreover, 26 loci in the TNFSF11 gene were in linkage disequilibrium with rs1021188, revealing relative similarities between different populations. Significant differences in both DNA methylation and unmethylation status were detected with 4.53- and 4.83-fold decreases in the global DNA methylation levels in female and male OTSC groups, respectively. These changes could contribute to an increased risk of OTSC development. Bioinformatic analyses indicated that each of the rs1021188 variations and the DNA methylation changes in the promoter CpG-sites within TNFSF11 may play an important role in its transcription regulation. To our knowledge, this is the first study that investigates an independent effect of the rs1021188 polymorphism and DNA hypomethylation of TNFSF11 promoter in OTSC. Genetic and epigenetic changes in the regulatory regions of TNFSF11 could offer new molecular insights into the understanding of the complexity of OTSC.